A Survey of Perceived Barriers and Attitudes Toward Mental Health Care Among OEF/OIF Veterans at VA Outpatient Mental Health Clinics. Issue 3 (1st March 2014) - Garcia, Hector A.; Finley, Erin P.; Ketchum, Norma; Jakupcak, Matthew; Dassori, Albana; Reyes, Stephanie C.
ABSTRACT: Objective: In an effort to improve our understanding of perceived treatment barriers among veterans of Operations Enduring Freedom and Iraqi Freedom (OEF/OIF) relative to other era veterans, the current study examined veteran attitudes and beliefs about mental health treatment and treatment-seeking, and perceived patient and institution-level logistical barriers to care. Method: A survey was conducted among 434 Combat veterans seeking care in nine Veterans Affairs mental health care outpatient clinics. Results: When compared to Vietnam and Gulf War veterans, OEF/OIF veterans were significantly more likely to endorse negative treatment attitudes as possible barriers to care. OEF/OIF veterans were also more likely than Vietnam veterans to endorse conflicting work demands as a potential barrier, although this was the only logistical barrier for which OEF/OIF veterans' responses differed significantly from those of veterans of other eras. Among OEF/OIF veterans, older veterans were more likely than younger veterans to endorse barriers related to cost and time commitments. Conclusions: These findings suggest an important role for outreach and engagement strategies that address attitudinal barriers to treatment utilization among veteran populations.